INTERNATIONAL EXPERIENCE OF E-GOVERNMENT (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2025)
In today's digital age, e-government is transforming the way governments interact with citizens, making public administration more transparent, efficient, and accessible. This article explores the benefits, challenges, and future prospects of digital governance, highlighting its role in reducing corruption, streamlining services, and fostering citizen engagement. While e-government offers numerous advantages, it also faces obstacles such as cybersecurity risks and digital inequality. With emerging technologies like artificial intelligence and blockchain, the future of e-government promises even greater innovation and efficiency. In this article written how digital transformation is reshaping governance worldwide.
Keywords: e-government; e-residency; blockchain-based; E-Government Development Index; United Nations; NemID; MyInfo